Challenges of organized environmental crime - Bugarski, Tatjana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
Environment as the totality of natural and man-made values ​​and their relationships, is a complex problem that is not just a challenge for the law in the sense that it is protected from intrusion, but also for the negative social phenomena such as crime. Dynamic negative social phenomenon, immanent to every society, crime is constantly in the process of "adaptation" in terms of modification of existing and creation of new forms. One of the contemporary forms of crime is an environmental crime which multiplies its concrete forms of manifestation, which is due to the extraordinary diversity of the environment in which offenders constantly find new enforcement cases. Especially significant issues regarding the environment is waste whose collection, transport, treatment and disposal is one of the priority importance for humanity. However, insufficient awareness of the significance and importance of this issue, as well as the harmful consequences of failure in connection with the waste in an appropriate manner, together with the motive of greed is enough for offenders to deal with illegal activity and exercise in relation to different types of waste. In this type of criminal activity usually occur organized criminal group that this type of criminal activity makes it even more difficult. These problems are extremely important and complex, in this paper, attention is given to the organized environmental crime in connection with smuggling of hazardous waste, as one of the forms of organized environmental crime.